Sustainable design of pipelines : guidelines for achieving advanced functionality - Schwarz, Walt; White, Patrick (Civil engineer); Mihm, Mark S. (ASCE manuals and reports on engineering practice, 2022)
"MOP 151 details the sustainable design and construction of pipelines and presents methods, practices, and decisions that influence and guide sustainable planning, design, construction, and operation, including the Envision infrastructure sustainability rating system"--